The Implementation of Bedsra Teaching Strategies in Reading comprehension at the Second Grade Students of SMP N 2 Kota Jambi in Academic Year 2018-2019 - Eka Deli; Suyadi Suyadi (Universitas Batanghari Jambi, 2020)
Teaching strategy was very much important for smoothed transaction of curriculum. Teaching strategies was a learning activity that must be done by the teacher and student, so that the learning objectives can be achieved effectively and efficiently. teaching strategies were approaches to teaching students. Reading comprehension was the act of understanding what you were reading. While the definition can be simply stated the act was not simple to teach, learn or practice. Reading comprehension was an intentional, active, interactive process that occurs before, during and after a person reads a particular piece of writing. This purpose this research is to know students’ ability about new strategies Bedsra in Reading. The population in this research is student of SMP N 2 KOTA JAMBI in Academic Year 2018-2019. This research uses Experimental Method, the sample of this research is 36 students class VIII B. The researcher uses quantitative method. The data of this research is collected through test. That is pre-test and post-test about narrative text. The result of this research is knowing about new strategies that is Bedsra in teaching reading comprehension. There is progress score from students’ pre-test to students’ post-test score. The average students score for pre-test is 80 with category B. The average post-test score is 40 with category D. The result of the “t-test matched” is 10,34. The number is higher than t table namely 2.03. So Ha is accepted and Ho is rejected.Key words: Bedsra, Teaching Strategies, Reading Comprehension.